Brewer’s spent grain as an ingredient in the development of bakeries. Impact of labeling on purchase intention and acceptability (INNOTEC, 2018)
The objective of this work was to revalue the waste generated by the brewing industry as a new ingredient rich in fibre and proteins for the development of bread. The eﬀect of nutritional warnings used as front of pack nutritional information on the acceptability and purchase intention of the developed products were evaluated considering the claim “fibre source” and sodium warning. Breads were made with BSG (Brewer’s spent grain), complying the claim “source of fibre”, bread enriched with fbre and bread without incorporation of BSG. Acceptability test among them showed that bread “source of fibre” presented a value signifcantly lower than the bread without incorporation of BSG and bread enriched with fibre, which did not present signifcant diﬀerences between them. In the case of acceptability and purchase intention evaluation considering nutritional information, it was observed that the presence of warning “excess salt” represented on the packaging decreases the intention of consumers to buy that kind of product, while the presence of the claim “fibre source” would increase it. It is an opportunity for the industry, who should focus eﬀorts towards the reformulation and/or development of acceptable products.
Keywords: Brewer´s spent grain; fibre; bread; labeling